Medications for hypertension of hemodialysis patients in Cáceres - Mato Grosso, Brazil - Vilella Hartwig, Shaiana; Lescano de Sousa Junior, Alcione; Ignotti, Eliane (O Mundo da Saúde, 2018)
Blood pressure in hemodialysis patients is difficult to control. The adequate use of antihypertensive drugs, associated with a good control of blood volume, are the most appropriate measures for the control of blood pressure in these patients. to objective describe the main drug classes used to control hypertension and to describe the epidemiological profile of chronic kidney disease patients on hemodialysis in the city of Cáceres-MT in the year 2014. Descriptive, cross-sectional epidemiological study with patients underwent hemodialysis in 2014 in the city of Cáceres, by means of patient medical records of a total of 17,134 hemodialysis sessions with 133 patients. The majority were male, black, married, with a mean age of 55 years, with hypertensive nephrosclerosis as the underlying disease. The main comorbidity was diabetes mellitus; 80% are diagnosed of end-stage chronic kidney disease; the mean time on hemodialysis (survival) was 4.8 years and 78.6% were hypertensive. Among hypertensive patients, 41.8% used a combination of two antihypertensive drugs and 32.6% used monotherapy; the adrenergic inhibitors class used was 27.1%, and 12.5% received diuretics. There was a mean survival of 5.2 years for hypertensive patients. The drug therapy used to control blood pressure complies with international recommendations in 81.6% of cases. The characteristics of patients being treated are similar to the other cities in the country. The mean survival of the hypertensive group of patients was higher than that of the non-hypertensive group.